PROGNOSTIC VALUE OF SHAPE-DESCRIPTIVE FACTORS FOR THE PROGRESSION OF GEOGRAPHIC ATROPHY SECONDARY TO AGE-RELATED MACULAR DEGENERATION. Issue 8 (August 2019) - Pfau, Maximilian; Lindner, Moritz; Goerdt, Lukas; Thiele, Sarah; Nadal, Jennifer; Schmid, Matthias; Schmitz-Valckenberg, Steffen; Sadda, SriniVas R.; Holz, Frank G.; Fleckenstein, Monika
Abstract : Purpose: To systematically compare the prognostic value of multiple shape-descriptive factors in the natural course of the disease. Methods: A total of 296 eyes of 201 patients (female patients 130; mean age: 72.2 ± 13.08 years) with a median follow-up of 2.38 years from 2 prospective, noninterventional natural history studies (Fundus-Autofluorescence-in-Age-related-Macular-Degeneration [clinicaltrials.gov identifier NCT00393692], Directional-Spread-in-Geographic-Atrophy [NCT02051998]) were included in the analysis. Serial fundus autofluorescence images were annotated using semiautomated image analysis software to determine the lesion area, circularity, perimeter, and caliper diameters. These variables and the fundus autofluorescence phenotype were evaluated for prediction of the future square root progression rates using linear mixed-effects models. Results: For the combined model, leave-one-out cross validation on patient level (Scenario 1: previously unknown patient) resulted in a goodness-to-fit (R 2 value) of 0.244 and leave-one-out cross validation on visit level (Scenario 2: previous observation of the patient) in a R 2 value of 0.391. This indicated that shape-descriptive factors could explain 24.4% of the variance in geographic atrophy progression in previously unknown patients and 39.1% in patients with previous observation. Conclusion: These findings confirm the relevance of shape-descriptive factors and previous progression as prognostic variables for geographic atrophy progression. However, a substantial part of the remaining variation in geographic atrophy progression seems to depend on other variables, some of which are visible in optical coherence tomography. Abstract : Supplemental Digital Content is Available in the Text.Fundus autofluorescence imaging allows for fully automated prediction of geographic atrophy progression rates based on annotations that are already used in clinical routine and that are part of the eligibility assessment of currently ongoing trials.